2008
DOI: 10.1007/s10404-008-0329-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of viscosity effect on droplet formation in T-shaped microchannels by numerical and analytical methods

Abstract: Both numerical and analytical models have been developed to explore the viscosity effect of the continuous phase on drop formation at a T-shaped junction in immiscible liquids. The effects of the generalized power law coefficient, the power law exponent and the yield stress on the mechanism of drop breakup, final drop size and frequency of drop formation are studied by using the numerical three-dimensional volume of fluid model. Droplets coalescence in Bingham fluids is observed in the beginning transient peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 28 publications
2
57
0
1
Order By: Relevance
“…The shift in the boundary between the plug and the parallel flows with the polymer addition could be due to both the change in the shear viscosity and the nonNewtonian rheology of the aqueous continuous phase. Sang et al, 32 from numerical analysis of droplet formation, found that an increase in Newtonian viscosity delayed the drop break up at the channel inlet and resulted in a decrease in the area of plug flow in the map. However, when power law fluids were used, as the flow behavior index, n, decreased (or the amount of polymer increased), the droplets broke closer to the Tjunction and extended the region of plug flow.…”
Section: Flow Pattern Mapmentioning
confidence: 99%
“…The shift in the boundary between the plug and the parallel flows with the polymer addition could be due to both the change in the shear viscosity and the nonNewtonian rheology of the aqueous continuous phase. Sang et al, 32 from numerical analysis of droplet formation, found that an increase in Newtonian viscosity delayed the drop break up at the channel inlet and resulted in a decrease in the area of plug flow in the map. However, when power law fluids were used, as the flow behavior index, n, decreased (or the amount of polymer increased), the droplets broke closer to the Tjunction and extended the region of plug flow.…”
Section: Flow Pattern Mapmentioning
confidence: 99%
“…The static contact angle between the two phases and the wall influences the droplet growth in the dispersed and continuous phase channel. It has been observed that the effect of contact angle in the droplet formation is negligible when its value is greater than 165 o (Sang et al, 2009). The value of static angle used in the present simulation has been set to 170 o .…”
Section: Boundary and Initial Conditionsmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) methods have also been used to simulate and analyze droplet generation in microfluidic channel configurations (Sang et al 2008;Kashid et al 2010; Zhou et al 2006;de Menech et al 2008;Gupta and Kumar 2010).…”
Section: Introductionmentioning
confidence: 99%